Implementation of Law Enforcement in Combating Criminal Acts of Forgery of Motor Vehicle Documents in the Jurisdiction of the Batang Police - Darwys, Muhammad Tomy Naufal; Wahyuningsih, Sri Endah (Jurnal Hukum Khaira Ummah, 2025)
The purpose of this study is to determine and analyze the implementation of law enforcement in overcoming the crime of falsification of motor vehicle documents in the jurisdiction of the Batang Police, the obstacles faced by police investigators in overcoming the crime of falsification of motor vehicle documents in the jurisdiction of the Batang Police, and the obstacles faced by police investigators in overcoming the crime of falsification of motor vehicle documents in the jurisdiction of the Batang Police. This study uses a sociological legal approach method, with analytical descriptive research specifications. The data used are secondary data obtained through literature studies and primary data obtained from interviews with respondents related to law enforcement of criminal acts of forgery of motor vehicle documents in the jurisdiction of the Batang Police. The formulation of the problem is analyzed using the theory of law enforcement and Criminal Responsibility in Islam. The results of this study are that the handling of motor vehicle document forgery cases by the Batang Police has been carried out in accordance with criminal law provisions, specifically referring to Article 263 of the Criminal Code. The legal process is carried out systematically, starting from the stages of investigation, inquiry, prosecution, to court decisions. In the Decision of the Batang District Court Number: 182 / Pid.B / 2024 / PN Btg, the defendant Waryono bin Yakub was legally and convincingly proven to have committed the crime of making and using fake documents, and was sentenced to one year in prison. From an Islamic legal perspective, this act of forgery is included in the category of ta'zir crimes, namely violations whose punishment is determined by the judge, because these actions are contrary to the values of honesty and justice in Islam. Batang Police investigators face various obstacles such as perpetrators who move from place to place, a neat and organized forgery network, lack of information from the public, and limited facilities, infrastructure, and human resources. To overcome these obstacles, the Batang Police have made various efforts such as routine raids, cross-agency cooperation, community outreach, and intelligence infiltration into the perpetrators' network.